The Impact of Specific Gut Microbiota Metabolites on Chronic Kidney Disease Progression: Novel Diagnostic Biomarkers and Therapeutic Targets - Daria Dąbkowska; Agnieszka Mioskowska; Joanna Szydziak; Aleksandra Hrapkowicz; Kinga Janowska; Olga Szeidl; Dominika Rehan; Julia Wołoszczak (Journal of Education, Health and Sport)
Introduction: Chronic kidney disease is characterized by an irreversible and gradually progressive process. Recent research has highlighted the role of metabolites derived from the intestinal microbiota as important factors in the progression of this disease. Consequently, numerous studies have focused on the impact of the microbiota, its diagnostic potential, and its therapeutic applications.